147k views
2 votes
Solve the system by substitution. x—5=y -3x—y= -19

User SkaveRat
by
6.1k points

1 Answer

4 votes

\begin{gathered} x-5=y \\ -3x-y=-19 \\ x-y=5\ldots\ldots\ldots\ldots.......(1) \\ -3x-y=-19\ldots.\ldots\ldots....(2) \\ x=5+y \\ -3(5+y)-y=-19 \\ -15-3y-y=-19 \\ -15-4y=-19 \\ -4y=-19+15 \\ -4y=-4 \\ y=(-4)/(-4) \\ y=1 \\ x-5=y \\ x-5=1 \\ x=1+5 \\ x=6 \end{gathered}

User Bharat
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.